New developments in immunotherapy for pediatric solid tumors. Issue 1 (February 2018) - Schultz, Liora M.; Majzner, Robbie; Davis, Kara L.; Mackall, Crystal
Abstract : Purpose of review: Building upon preclinical advances, we are uncovering immunotherapy strategies that are translating into improved outcomes in tumor subsets. Advanced pediatric solid tumors carry poor prognoses and resultant robust efforts to apply immunotherapy advances to pediatric solid tumors are in progress. Here, we discuss recent developments in the field using mAb and mAb-based therapies including checkpoint blockade and chimeric antigen receptors (CARs). Recent findings: The pediatric solid tumor mAb experience targeting the diganglioside, GD2, for patients with neuroblastoma has been the most compelling to date. GD2 and alternative antigen-specific mAbs are now being incorporated into antibody–drug conjugates, bispecific antibodies and CARs for treatment of solid tumors. CARs in pediatric solid tumors have not yet achieved comparative responses to the hematologic CAR experience; however, novel strategies such as bispecific targeting, intratumoral administration and improved understanding of T-cell biology may yield enhanced CAR-efficacy. Therapeutic effect using single-agent checkpoint blocking antibodies in pediatric solid tumors also remains limited to date. Combinatorial strategies continue to hold promise and the clinical effect in tumor subsets with high antigenic burden is being explored. Summary: Pediatric immunotherapy remains at early stages of translation, yet we anticipate that with advanced technology, we will achieve widespread, efficacious use of immunotherapy for pediatric solid tumors.